Localization of the Khazar cities - from Sarkela to Samandar - O. Dm. Fedchenko (Nomadic Civilization: Historical Research)
In this article, on the basis of various historical evidence, the location of the Khazar cities is studied. A comprehensive description of the geographical objects indicated in ancient documents makes it possible to determine their localization. The data of Persian and Arab historians and chroniclers have been studied. The routes of the Arab armies, which made campaigns against the Khazar possessions, were studied. The analysis of the mentioned landmarks made it possible to find out the localization of the cities and regions of al-Khasin, Bar’uza, Balanjar, Vabandar, Samandar, al-Bayda. On the basis of written sources, the approximate borders of the “internal” Khazaria and the external limits to which the Khazar influence extended were established. The localization of the Sarkel fortress, which acted as a military and commercial outpost in the Black Sea region, was determined. The location of the Khazar capital Itil, located in front of the Volga delta, was established. It was determined that Balanjar, one of the early Khazar capitals, was located on the territory of the present city of Makhachkala. The location of Samandar, located on the right bank of the Sulak River, on the Khodum mountain of the Nadyrbek ridge, was revealed. Along with historical sources, the author draws on the results of modern research from related fields. The proposed article gives a fresh impetus to the study of the archaeological data of the region under consideration, allows us to take a fresh look at old problems.